2019
DOI: 10.1097/nmd.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Behavioral Therapy on Improving the Cognitive Function in Major and Minor Depression

Abstract: The aim of this study was to investigate the effectiveness of cognitive behavioral therapy (CBT) on improving the cognitive function in minor depression (MiD) and major depression (MaD). The study will constitute a placebo-controlled single-blind parallel-group randomized controlled trial. The selected participants will be randomly allocated into one of two parallel groups with a 1:1 ratio: the CBT-based group and the general health education group. CBT significantly alleviated depressive symptoms of MiD and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another study found a brief CBT intervention to be more effective than usual care at reducing illness intrusiveness in patients with chronic obstructive pulmonary disease (Renn et al, 2018). Research has also discovered that CBT can lead to enhancements in cognitive functioning as well as improvements in mood (He et al, 2019), and that improvements in depressive symptoms can lead to improvements in cognitive functioning over time (Douglas & Porter, 2009). Therefore, evidence from research has demonstrated that CBT can be an effective intervention for not only enhancing mood, but also potentially reducing perceived illness intrusiveness and enhancing cognitive functioning.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Another study found a brief CBT intervention to be more effective than usual care at reducing illness intrusiveness in patients with chronic obstructive pulmonary disease (Renn et al, 2018). Research has also discovered that CBT can lead to enhancements in cognitive functioning as well as improvements in mood (He et al, 2019), and that improvements in depressive symptoms can lead to improvements in cognitive functioning over time (Douglas & Porter, 2009). Therefore, evidence from research has demonstrated that CBT can be an effective intervention for not only enhancing mood, but also potentially reducing perceived illness intrusiveness and enhancing cognitive functioning.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Two reviewed studies examined the effects of CBT, with one examining changes in 'cold' functions and the other examining 'hot' neurocognitive processes. He et al (2019) reported the effects of CBT and General Health Education (GHE) versus GHE alone, on a range of neuro cognitive functions in patients with DSM-IV minor or major depression. Neurocognitive function improved over time in both treatment groups, with retesting completed at 12, 24, 36 and 60 weeks.…”
Section: Studies In Patients On Concomitant Medicationmentioning
confidence: 99%
“…According to the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), major depressive disorder or major depression is described by a group of symptoms affecting a person’s ability to study, eat, sleep, work, and enjoy previous pleasurable activities and is disabling and preventing a person from normal functioning (American Psychiatric Association (APA, 2013)). Moreover, persistent depressive disorder is described by long-term (2 years or longer) symptoms that may not be sufficiently severe to disable a person but can affect functioning or feeling (APA, 2013; He et al, 2019; Vandeleur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%